Digitalization of the educational process in institutions of postgraduate medical education - Kharkivskiy, V. (Problems of Engineer-Pedagogical Education, 2021)
The specifics of the professional activity of medical professionals, which determines the need for continuing education, creates the need to modernize the system of postgraduate medical education. Implementation of the program of digital economy development and digitalization of health care in accordance with the priorities of state policy poses new tasks for postgraduate education, the solution of which is possible with a comprehensive approach to its digitalization. Systematic and productive use of information and communication and digital technologies will allow the components of scientific and educational processes to respond quickly to changing conditions in the digital world and quickly make decisions aimed at quality training of competitive medical personnel. The system of postgraduate medical education has an important reform process aimed at expanding the capabilities of traditional models of education based on the creation of a single digital educational space. The article analyzes the phenomenon of digitalization, which rapidly covers the system of education in general and postgraduate medical education in particular. Based on the analysis, synthesis, observation, description and comparison, the author identifies the possibilities of digitalization of the educational process in postgraduate medical education institutions. The obtained results confirm that the digitalization of postgraduate medical education is a long process characterized by the need for comprehensive transformations. First of all it is necessary to begin with the main process of activity of establishment of postgraduate medical education – educational process. The author understands the digitalization of the educational process as the transformation of the educational process and its elements, on the one hand, and digital technologies and tools used in the institution of postgraduate medical education, on the other. The study is also devoted to the possibilities and prospects of introducing online learning in the educational process of postgraduate medical education. The author demonstrates the peculiarities of the application of the main structural and functional elements of electronic training courses in postgraduate medical education.